1999
DOI: 10.7326/0003-4819-131-11-199912070-00002
|View full text |Cite
|
Sign up to set email alerts
|

Guanylyl Cyclase C Messenger RNA Is a Biomarker for Recurrent Stage II Colorectal Cancer

Abstract: Expression of guanylyl cyclase C mRNA in lymph nodes is associated with recurrence of colorectal cancer in patients with stage II disease. Analysis of guanylyl cyclase mRNA expression by RT-PCR may be useful for colorectal cancer staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
96
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 26 publications
1
96
1
3
Order By: Relevance
“…RNA was extracted from tissues by a modification of the acid guanidinium thiocyanate-phenol-chloroform extraction method (19,23). Briefly, individual tissues were pulverized in 1.0 mL Tri-Reagent (Molecular Research Center, Cincinnati, OH) with 12 to 14 sterile 2.5-mm zirconium beads in a bead mill (Biospec, Bartlesville, OK) for 1 to 2 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted from tissues by a modification of the acid guanidinium thiocyanate-phenol-chloroform extraction method (19,23). Briefly, individual tissues were pulverized in 1.0 mL Tri-Reagent (Molecular Research Center, Cincinnati, OH) with 12 to 14 sterile 2.5-mm zirconium beads in a bead mill (Biospec, Bartlesville, OK) for 1 to 2 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, GCC may fulfill the criteria for a sensitive and specific prognostic and predictive marker for identifying occult colorectal micrometastases (12). Indeed, in a retrospective analysis, detection of GCC expression by qualitative RT-PCR in lymph nodes free of metastases by histopathology was highly associated with the development of recurrent colorectal cancer (23).…”
mentioning
confidence: 99%
“…In intestine, GC-C is expressed along a crypt-to-villus gradient, with the greatest expression in the mid-villus where enterocytes transition from proliferation to differentiation, suggesting that GC-C may play a role in regulating that transition (22,23). Also, expression of GC-C is highly conserved, whereas that of guanylin is significantly reduced, in proliferating colorectal cancer cells and tumors (10,(24)(25)(26)(27). In addition, oral uroguanylin reduced the formation of polyps in the Min͞ϩ mouse model of colon cancer (27).…”
mentioning
confidence: 99%
“…This hypothesis is supported by a report by Rosenberg et al (2002), who found CK-positive cells on histological examination exclusively on the outside of lymph nodes in almost 30% of RT -PCR-positive specimens. Other markers, including CEA, MUC2, GCC, matrilysin, b-HCG and others, have been explored to detect lymph node micrometastases by RT -PCR and yielded inconsistent results (Ichikawa et al, 1998;Cagir et al, 1999;Bernini et al, 2000). Expression levels of these different markers can vary considerably among tumour specimens of the same entity.…”
Section: Discussionmentioning
confidence: 99%